Gambaran Efek Samping Kontrasepsi Hormonal pada Akseptor Keluarga Berencana di Wilayah Puskesmas X Kabupaten Karanganyar - Lucia Vita Inandha Dewi; Eunike Yuvita Purbosari; Inaratul Rizkhy Hanifah (Fakultas Farmasi Universitas Setia Budi, 2022)
Hormonal contraception use in the Family Planning (KB) program can cause side effects that interfere with health, reduce comfort, and cause the program to stop, in several previous studies, weight gain and menstrual disorders have been reported as the most side effects, but it is suspected that there are still side effects. For others that have not been reported, a complete description of the incidence of side effects is needed to consider the selection of a safe and suitable type of contraception for the acceptor. The purpose of the study was to describe the incidence of side effects and the percentage of events based on the type of hormonal contraception. This research is an observational descriptive study involving 327 respondents according to the inclusion criteria, using a questionnaire that has been tested for validity and reliability. The study was conducted on family planning acceptors who are in the working area of ​​Puskesmas X Surakarta. Analysis of the results was carried out univariately by the percentage of the number of adverse events based on the type and type of hormonal family planning used. The results showed that the incidence of side effects in the form of weight gain was 51.8%,, menstrual disorders 38.8%, dizziness 9.1%, nausea 7%, acne 6,1%, and anxiety was 3%. Based on the type of hormonal contraception, the incidence of side effects experienced by acceptors of 3-month injections was 74,3 %, 1-month injections 38,8%, pills 29,9%, and implants was 6,4%.